WHEN THERE IS A NEED TO CODIFY LEGISLATION? (ON THE EXAMPLE OF UZBEKISTAN AND KYRGYZSTAN - Mavluda Akhmedshaeva; Kuldysheva Gulsara Kenzheevna (Scholar Express Journals, 2024)
Due to the complication and rapid development of social relations, the array of legal acts aimed at regulating new complex social relations in the context of digitalization is correspondingly increasing. This, in turn, can lead to certain difficulties in the enforcement process. Therefore, it is very important that law enforcement entities, if necessary, quickly and accurately apply the relevant rules. Consequently, the issue of effective systematization of legislation is becoming particularly relevancet at the present stage. This article will examines the issues of the codification process in Uzbekistan and Kyrgyzstan from the point of view of comparative law. One of the important forms of systematization of legislation is codification. At the same time, in legal science there is no holistic doctrine of codification, including when and on what grounds the need for codification arises. Several proposals and conclusions have been formulated aimed at improving the codification process and its scientific research as a whole.
Keywords: codification; necessary; improving; process